International accounting standards: What is convergence and whether there is any likelihood of convergence between the EU and the US? - Khankishiyev, Vusal (2016)
Since the promulgation of the International Financial Reporting Standards (IFRS) by the International Accounting Standards Board (IASB), the IFRS has been adopted as the definitive accounting standard by a number of jurisdictions, most notably within the EU. The most significant country that has not yet adopted the IFRS is the United States which has had a tradition of strong accounting standards in the form of the US Generally Accepted Accounting Principles (US GAAP). IFRS and US GAAP have significantly different approaches towards regulation with IFRS taking a principles-based approach towards regulation while US GAAP has traditionally been rules-based in its approach. In practice, this means that IFRS tends to be shorter than US GAAP. The US GAAP relies on bright-line tests and explicitly stated industry-based exceptions towards classification, measurement, and impairment rules while the IFRS focuses mostly on the economic effects of transactions rather than explicitly stated tests or the legal form of the accounting event. This study reviews the similarities and discrepancies between the accounting treatment of leases and financial assets between the recently announced IFRS and US GAAP accounting standards. Through a comparison of the regulations related to each accounting transaction, this study concludes that the prospects for convergence between IFRS and the US GAAP are weak. This is because there are significant signs that the US GAAP remains rules-based in its approach, which suggests the possibility that companies will have to maintain two sets of accounts if they were simultaneously active in both regions.